2020
DOI: 10.21203/rs.2.21966/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review of the association between fibromyalgia and functional gastrointestinal disorders

Abstract: Background Fibromyalgia and functional gastrointestinal disorders are frequently encountered in clinical settings. Common to both is significant burden on individuals and health care systems, an elusive aetiology and several comorbid conditions. While a relationship between irritable bowel syndrome and fibromyalgia has been demonstrated, a broader review of the relationship between fibromyalgia and other functional gut disorders has not been undertaken. Objectives This paper reports a systematic review of the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Fibromyalgics present with constipation at up to double the rate of those with diarrhoea [11,70], which correlates with severity of fibromyalgia symptoms [70]. Constipation is associated with higher methane production [71], yet both Pimentel's studies reported elevations in hydrogen gas [17,69].…”
Section: Small Intestinal Bacterial Overgrowthmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibromyalgics present with constipation at up to double the rate of those with diarrhoea [11,70], which correlates with severity of fibromyalgia symptoms [70]. Constipation is associated with higher methane production [71], yet both Pimentel's studies reported elevations in hydrogen gas [17,69].…”
Section: Small Intestinal Bacterial Overgrowthmentioning
confidence: 99%
“…Fibromyalgia is associated with a range of somatic symptoms and gastrointestinal disorders. Our group have recently conducted a systematic review of the comorbidity of FGID in fibromyalgia and found this area to be under-explored, with the majority of studies focusing on irritable bowel syndrome (IBS) [11]. IBS has been associated with alterations in the composition and diversity of the gastrointestinal microbiota [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fibromyalgics present with constipation at up to double the rate of those with diarrhoea (12,69), which correlates with severity of fibromyalgia symptoms (69). Constipation is associated with higher methane production (70), yet both Pimentel's studies reported elevations in hydrogen gas (26,68).…”
Section: Small Intestinal Bacterial Overgrowthmentioning
confidence: 99%
“…Individuals with comorbidity report higher symptom severity and poorer quality of life (10,11). To date, the majority of studies on FGIDs have focused on irritable bowel syndrome (IBS) (12), which has been associated with alterations in the composition and diversity of the gastrointestinal microbiota (13).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, women with endometriosis are more sensitive to pain and susceptible to chronic pelvic pain [ 44 ]. In addition, there is a consensus that fibromyalgia is more prevalent in women [ 45 ], and treatment of dysmenorrhea with hormonal contraceptives can reduce the risk of fibromyalgia [ 46 ]. These phenomena indicate that estrogen may contribute to inflammatory pain.…”
Section: Effects Of Ers In Different Modalities Of Painmentioning
confidence: 99%